UPAYA MENINGKATKAN IMAN DAN MOTIVASI BELAJAR DENGAN IMPLEMENTASI RUQYAH SYARIYYAH DALAM PEMBELAJARAN PAI - Rizal Dalil (MGMP PAI Jawa Barat, 2023)
Islamic Religious and Character Education aims to educate students to become people of faith, have noble character, and have the life skills needed in their lives to be successful in this world and the hereafter. However, unfortunately there are still many PAI teachers who tend to focus on teaching theoretically, lack practice and do not provide life skills that are very interesting and needed by students. Therefore, the author feels challenged to create best practices that aim to increase students' faith and learning motivation by implementing Ruqyah Syar'iyyah in fun and meaningful learning on the teaching material of Faith in the Angels of Allah SWT. in class VII-G odd semester, SMPN 1 Kota Bogor. Based on the results of this best practice, it can be concluded that the implementation of Ruqyah Syar'iyyah in PAI learning can increase students' faith and motivation to learn. This is proven based on student responsse questionnaire data, namely that all students (100%) feel calm and only fear Allah SWT after participating in the lesson. Apart from that, the majority of students considered that learning was very enjoyable (70%) and enjoyable (30%) so they were motivated to learn.